2008
DOI: 10.1080/17543260801998855
|View full text |Cite
|
Sign up to set email alerts
|

Assessing functional clothing needs of bicycle patrol officers

Abstract: Bicycle police patrol officers require functional occupational clothing to perform a variety of daily tasks. Vonk (2003) reported officers' difficulty with finding specialised uniforms. The purpose of this study was to identify the needs specific to bicycle patrol officers for uniforms that address instrumental and expressive performance requirements. Survey data were collected from 238 United States bicycle patrol officers in 29 units from 15 states across the country. Officers expressed neutral to moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Moreover, this study placed equal premium on fabric and design rather than on design only, which has been practiced in previous studies (Huck and Kim 1997, Choi and Ashdown 2002, Tan et al1998, Black and Cloud 2008 The predicted e and humidity tual T-shirt. Figure 6B.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, this study placed equal premium on fabric and design rather than on design only, which has been practiced in previous studies (Huck and Kim 1997, Choi and Ashdown 2002, Tan et al1998, Black and Cloud 2008 The predicted e and humidity tual T-shirt. Figure 6B.…”
Section: Discussionmentioning
confidence: 95%
“…The design process of DeJonge (1984) was also applied to the assessment of functional clothing worn by bicycle patrol officers (Black and Cloud 2008), which involved influence factors that were particularly related to comfort, durability, protection, and dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…The results led to the redesign and improvement of the product, as well as the reduction of product returns. Other clothing items, such as occupational clothing for female pear farmers [16], thermal protective flight suits [17], and bicycle patrol uniforms [18], were designed to address the expectations of the wearer by employing the functional design process approach. Thus, the literature provides a systematic method to develop functional clothing.…”
Section: Introductionmentioning
confidence: 99%
“…Black and Cloud (2008) assessed the functional clothing needs of bicycle police officers and concluded that visible and robust equipment is important from a safety perspective as collisions are common causes for police cyclists' injuries, and without high visibility police officers may risk injuring both themselves and the general public. However, demands for visibility can also be contrasted with tactical advantages of riding 'stealth'.…”
Section: Previous Research On Police Bicycle Patrolsmentioning
confidence: 99%